Peripheral Blood circRNA Microarray Profiling Identities hsa_circ_0001831 and hsa_circ_0000867 as Two Novel circRNA Biomarkers for Early Type 2 Diabetic Nephropathy - Zhang K; Wan X; Khan MA; Sun X; Yi X; Wang Z; Chen K; Peng L (Diabetes, Metabolic Syndrome and Obesity, 2022)
Keke Zhang,1 Xinxing Wan,1 Md Asaduzzaman Khan,2 Xiaoying Sun,1 Xuan Yi,1 Zhouqi Wang,1 Ke Chen,1 Lin Peng3 1Department of Endocrinology, the Third Xiangya Hospital of Central South University, Changsha, People’s Republic of China; 2The Research Centre for Preclinical Medicine, Southwest Medical University, Luzhou, People’s Republic of China; 3Department of Nephrology, the First Hospital of Changsha, Changsha, People’s Republic of ChinaCorrespondence: Lin Peng, Department of Nephrology, the First Hospital of Changsha, Changsha, People’s Republic of China, Tel +86-731-8466-7510, Email plin1018@163.com Ke Chen, Department of Endocrinology, the Third Xiangya Hospital of Central South University, Changsha, People’s Republic of China, Tel +86-731-8861-8239, Email chenke520@yeah.netPurpose: Type 2 diabetes mellitus (T2DM) increases the incidence of diabetic nephropathy (DN) and eventually progresses to end-stage renal disease. Circular RNAs (circRNAs) are a class of non-coding RNAs that are promising as diagnostic biomarkers and therapeutic targets for human diseases. The aim of this study was to analyze the differential expression of circRNAs (DECs) in peripheral blood from patients with early type 2 diabetic nephropathy (ET2DN), T2DM and controls, which will facilitate to discover some new biomarkers for ET2DN.Patients and Methods: Twenty ET2DN patients, 20 T2DM patients, and 20 normal controls were included in this study. Blood samples from 3 random subjects of age- and sex-matched patients in each group, respectively, were used to detect circRNA expression profiles by circRNA microarray, and the circRNA expression of remaining subjects was validated by real-time quantitative polymerase chain reaction (qRT-PCR). Further functional assessment was performed by bioinformatic tools.Results: There were 586 DECs in ET2DN vs T2DM group (249 circRNAs were upregulated and 337 circRNAs were downregulated); 176 circRNAs were upregulated and 101 circRNAs were downregulated in T2DM vs control group; 57 circRNAs were upregulated and 5 circRNAs were downregulated in ET2DN vs control group. The functional and pathway enrichment of DECs were analyzed by GO and KEGG. qRT-PCR results revealed that hsa_circ_0001831 and hsa_circ_0000867 were significantly upregulated in ET2DN group compared to both of T2DM and control group. The ROC curve demonstrated that hsa_circ_0001831 and hsa_circ_0000867 have high sensitivity and specificity associated with ET2DN.Conclusion: Our study showed the expression profiles of circRNAs in ET2DN patients and demonstrated that hsa_circ_0001831 and hsa_circ_0000867 can be used as novel diagnostic biomarkers for ET2DN.Keywords: circRNAs microarray, diagnostic biomarkers, early type 2 diabetic nephropathy, inflammation